Development of an eco-friendly health process for the treatment of excessive patological scars (Nexo Revista Científica, 2020)
An eco-friendly health process has been designed and implemented for the treatment of excessive pathological scars such as keloids, hypertrophic and inesthetic scars through the use of photons from sunlight as a non-invasive, safe and effective alternative technique in contrast to technical techniques currently used that may be ineffective and risky, that use chemical inputs, energy from non-renewable sources (electrical) and that, often problems of prolonged treatment times. This eco-friendly process oriented to the topic of health is made up of three constitutive units: unit of analysis, treatment and cutaneous rehabilitation, which includes from the identification of the pathology and its own characteristics (thickness, size, pigmentation, etc.); until the prescription of the appropriate treatment and rehabilitation for the affected area. The process uses sunlight for treatment and improvements in the recovery of the affected tissue are expected, thus overcoming the functional limitations caused, it also relieves pain and the disappearance of edemas by 100% and up to 90% improvement in consistency, thickness and appearance of the skin. The process can be applied to patients of any age, sex and in any state of health.